Affect of various storage conditions on aerobic mesophilic count of three varieties of cassava (Manihot esculenta Crantz) roots harvested from Miagao, Iloilo. - Juanitas, Mary Antonette B.
Three varieties of cassava, Manihot esculenta Crantz, (Lakan-1 (Malagyan), Lakan-1 (Paroon) and Golden yellow) harvested from two different locations in Miag-ao, Iloilo were stored in four storage conditions, open shelf, open shelf pruned, soil, and saw dust. The total aerobic mesophilic count of these cassava varieties stored at different conditions were then monitored starting from Day 0 and every two days thereafter until they were deteriorated. The results were analyzed using two-way and three-way ANOVA. Furthermore, the lag phase of the bacterial growth curve of each of the statistical analysis revealed that there is no significant difference on the mean microbial count among varieties with respect to the type of storage (open shelf, open shelf pruned, soil, and saw dust) and the duration of storage. Hence, it is recommended that the best storage condition of the cassava varieties was open shelf because of economic or monetary reasons. Moreover, it was also observed that the cassava varierty Lakan-1 (Malagyan) can be stored for as long as 20 days while the cassava varieties Golden yellow, and Lakan-1 (Paroon) can be stored for as long 9 days. Therefore, the best variety among the three was found to be Lakan-1 (Malagyan) and the best storage condition was open shelf.